In Vitro and in Silico Investigation of DNA Interaction, Topoisomerase I and II Inhibitory Properties of Polydatin. Issue 10 (23rd September 2022) - Şöhretoğlu, Didem; Barut, Burak; Sari, Suat; Özel, Arzu; Kuruüzüm‐Uz, Ayşe; Arroo, Randolph
Abstract: Polydatin or piceid, is the 3‐ O ‐glucoside of resveratrol and is found abundantly in grapes, peanuts, wine, beer, and cacao products. Although anticancer activity of polydatin was reported before, and potential antiproliferative mechanisms of polydatin have been proposed, its direct effects on DNA and inhibitory potential against topoisomerase enzymes have remained unknown. In this study we aimed to reveal the link between polydatin's effects on DNA and DNA‐topoisomerases and its antiproliferative promise. For this purpose, we evaluated the effects of polydatin on DNA and DNA topoisomerase using in vitro and in silico techniques. Polydatin was found to protect DNA against Fenton reaction‐induced damage while not showing any hydrolytic nuclease effect. Further, polydatin inhibited topoisomerase II but not topoisomerase I. According to molecular docking studies, polydatin preferably showed minor groove binding to DNA where the stilbene moiety was important for binding to the DNA‐topoisomerase II complex. As a result, topoisomerase II inhibition might be another anticancer mechanism of polydatin. Abstract :